Comparison of Fatigue Dimensions between Warehouse Staff and Heavy Equipment Technicians in The Mining Sector - Mohammad Ikram Bahari; Dewi Friska; Dewi Yunia Fitriani; Ahmad Fuady; Nuri Purwito Adi (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Work-related fatigue is a multidimensional condition that can reduce productivity and increase the risk of workplace accidents, particularly in professions with high physical and mental demands such as heavy equipment technicians and warehouse workers in the mining sector. Both professions work under shift systems and high workloads; however, studies comparing the dimensions of fatigue between the two remain limited.Objective: To determine the proportion of fatigue levels and compare fatigue dimensions between warehouse workers and heavy equipment technicians.Methods: A descriptive-comparative cross-sectional study was conducted on 132 male workers (100 heavy equipment technicians and 32 warehouse workers) at a mining company in South Kalimantan, Indonesia. Demographic and job-related characteristics were collected. Fatigue was measured using the Swedish Occupational Fatigue Inventory (SOFI) in Indonesian, which has been validated, covering five dimensions: energy deficiency, physical exertion, physical discomfort, sleepiness, and lack of motivation. Descriptive and comparative statistical analyses were conducted.Results: Mild fatigue (among technicians and warehouse staff were 90% and 93.8% ). Moderate fatigue was experienced by 10% of technicians and 6.3% of warehouse staff. No participants experienced severe fatigue. Among heavy equipment technicians, the highest dimension was physical exertion, while the highest dimension of fatigue among warehouse staff was lack of energy. Work factors, age, work experience, and nutritional status were not significantly associated with fatigue levels.Conclusion: Mild fatigue dominates in both work groups, as this company is a supporting company for a mining company, there have never been any near misses or incidents, and has an appropriate management. For the overall fatigue dimension, heavy equipment technicians scored higher than warehouse staff. However, fatigue checks should still be carried out regularly among workers.